De la démobilisation au réinvestissement « local ». Mouvements sociaux locaux et territoires au Chili - Emmanuelle Barozet (Cahiers des Amériques Latines)
In spite of a strong centralization, and a limited democratization, the local and territorial issue has forcefully established itself in Chile, within the scope of the research of new forms of citizen participation. Starting with the description of movements in defence of neighbourhoods in the big cities and the Mapuche mobilisation in the south, this article demonstrates that, in spite of examples of mobilisation that are taking shape, or that establish themselves at a local level, the tension between representative democracy and the demand for participatory mechanisms at a local level cannot surpass the traditional forms of governance.